Tearing down the 'buckskin curtain': domestic policy-making and Indigenous intellectuals in the Cold War United States and Canada. Issue 2 (2nd April 2020) - Humalajoki, Reetta
ABSTRACT: North American Indigenous peoples remain overlooked in Cold War scholarship, despite being tangibly impacted by this global conflict. This article presents a study of four foundational texts, to argue that the Cold War shaped the introduction of new destructive Indian policies in the United States and Canada, which aimed to eradicate the special legal status of Indigenous peoples. Moreover, Indigenous activist intellectuals like Vine Deloria, Jr. and Harold Cardinal successfully embedded their writing in the Cold War context of decolonisation and anti-communism to challenge harmful federal policy and the image of the United States and Canada as upholding 'freedom' and 'democracy'.